Halogen perovskite polycrystal synthesis method

By uniformly mixing high-purity PbBr2 and CsBr powders in a quartz boat, and controlling the reaction conditions using vacuum, inert gas and ultrasonic technology, the problem of low quality of halogen perovskite polycrystalline materials in the prior art is solved, and high The synthesis of polycrystalline materials with purity, no hemisphere and high light transmittance provides high-quality raw materials for single crystal growth.

CN119392367AInactive Publication Date: 2025-02-07HARBIN UNIV OF SCI & TECH +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411450121.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult to efficiently synthesize high-quality halogen perovskite polycrystalline materials in the prior art, resulting in low quality of raw materials for single crystal growth.

Method used

A halogen perovskite polycrystalline synthesis method is adopted. By uniformly mixing high-purity PbBr2 and CsBr powders in a quartz boat, and setting multiple temperature zones in the quartz tube, the reaction conditions are controlled using vacuum, inert gas and ultrasonic technology to ensure that The material reacts uniformly and purifies at high temperatures.

Benefits of technology

The synthesis of CsPbBr3 polycrystalline materials with high purity (above 5N), free of hexagrams and high light transmittance has been achieved, providing high-quality raw materials for single crystal growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392367A_ABST
    Figure CN119392367A_ABST
Patent Text Reader

Abstract

A halogen perovskite polycrystal synthesis method relates to the technical field of polycrystal growth and comprises a melt reaction stage, a synthesis solidification stage, an in-situ zone melting purification stage and a cooling stage. In the molten material reaction stage, the liquid sealing covering agent can effectively prevent powder and melt from volatilizing and drifting away in a high-temperature state, the phenomenon of component segregation during reaction is prevented, and redundant impurities and unreacted powder are absorbed; vacuum and inert gas achieve the purposes of balancing pressure and effectively controlling formation of impure phases and immersion of other impurities; ultrasonic waves enable the synthesis reaction to be more uniform and thorough. In the in-situ zone melting purification stage, the perovskite polycrystal material in-situ zone is circularly heated and cooled, the polycrystal material is circularly melted and solidified, a solid-liquid interface is gradually propelled from a temperature zone 1 to a temperature zone 7 by utilizing different segregation coefficients of impurities in crystals and along with the circular process of melting and solidification, the impurities are segregated towards two sides and enriched at two ends of the polycrystal material, and the purity of the polycrystal material is improved. Therefore, the purity of the synthesized polycrystal material is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polycrystalline growth, and in particular relates to a method for synthesizing halogen perovskite polycrystalline. Background Art

[0002] In recent years, halogen perovskites have become a widely studied type of optoelectronic material and have been applied in many disciplines. In particular, the most representative CsPbBr3 crystal has been widely studied. The crystal structure of CsPbBr3 is a typical ABX3 type perovskite structure. Single crystal growth is inseparable from the synthesis of polycrystalline materials. Qualified polycrystalline materials are the basis for growing high-quality single crystal materials. Therefore, the preparation of polycrystalline materials is particularly important. Summary of the invention

[0003] In order to achieve high-quality synthesis of halogen perovskite polycrystals, the present invention provides a halogen perovskite polycrystal synthesis method. The CsPbBr3 polycrystal material synthesized by the present invention has high purity (above 5N), no impurities, and high transmittance, thereby providing high-quality raw materials for single crystal growth.

[0004] The technical solution provided by the present invention comprises the following steps: Step 1: Evenly mix high-purity PbBr2 powder and high-purity CsBr powder according to the atomic molar mass ratio of PbBr2:CsBr 1:0.55-0.58 and put them into a quartz boat. At the same time, put a solid liquid sealing agent with a weight of 1 / 3 of the weight of the charge into the quartz boat. Place the quartz boat in a quartz tube with one end of the quartz tube made into a round head seal and the other end open; Step 2: placing the quartz tube obtained in step 1 into a polycrystalline synthesis furnace for perovskite, and installing a sealed connector at the open end of the quartz tube, wherein the polycrystalline synthesis furnace has seven temperature zones arranged in sequence along the furnace cavity; Step 3: The sealing connector is connected to the vacuum system, the inert gas filling system and the ultrasonic intervention system respectively, so that the vacuum system can evacuate the quartz tube, the inert gas filling system can introduce inert gas into the quartz tube, and the ultrasonic intervention system can transmit ultrasonic waves into the quartz boat; Step 4: After checking that all connections are in good condition, turn on the vacuum system and make the vacuum degree in the quartz tube reach 10 -5 pa, turn off the vacuum pump, turn on the inert gas filling system, fill the quartz tube with inert gas to raise its pressure to 0.1-0.15mpa, then use the temperature control system of the polycrystalline synthesis furnace to set the target parameters and temperature, turn on the power after confirmation, and the polycrystalline synthesis furnace starts to heat up; Step 5: Enter the melting reaction stage. All temperature zones are heated to 450°C in 30 minutes and kept at a constant temperature for 1 hour to wait for the solid liquid sealing covering agent to melt and become molten liquid. After 1 hour, the temperature is continued to rise. In 40 minutes, the temperature zone 1 near the connector is heated to 550°C, and the other temperature zones are heated to 670°C. In the process of gradually rising temperatures, high-purity PbBr2 powder and high-purity CsBr powder begin to gradually melt and react under the liquid liquid sealing covering agent. After the temperature stabilizes, the ultrasonic intervention system is turned on and the constant temperature ultrasound is performed for 2 hours. The ultrasonic wave contacts the loaded quartz boat through the quartz transmission rod and transmits the ultrasonic wave into the quartz boat. The material in the quartz boat will be excited by the ultrasonic wave and oscillate. The high temperature plus ultrasonic oscillation will accelerate the material and react more evenly. It can also make the impurities detach faster and be absorbed by the liquid sealing covering agent, thereby reducing the component segregation of the material and improving the purity. The ultrasonic frequency is 80-90KHZ. Step 6: After 2 hours of constant temperature ultrasound, observe the temperature. When there is no abnormal pressure, turn off the ultrasonic intervention system and enter the next synthesis solidification stage. Enter the synthesis solidification program in the temperature control system. The temperature zones of the entire polycrystalline synthesis furnace will be slowly cooled down in an orderly manner according to the synthesis solidification program. Starting from the temperature zone close to the sealed connector, the temperature zones are 1, 2, 3, 4, 5, 6, and 7. The temperature of temperature zone 1 is cooled at a cooling rate of 4℃ / h for 24 hours. When the temperature drops to 450-500℃, it remains at a constant temperature. The temperature zones 2, 3, 4, 5, 6, and 7 are cooled down in the order of 2.3.4.5.6.7 at intervals of 0.5 hours, and cooled at a cooling rate of 9℃ / h for 24 hours. When the temperature of each temperature zone drops to 450-500℃, it remains at a constant temperature. The pressure must be kept constant throughout the synthesis stage. If there is a change, the inert gas filling system must be inflated or deflated at any time to always control the pressure at the initial value before synthesis; Step 7: Determine whether the synthesis is completed by temperature. When all the measured temperatures are between 450-500°C, it can be determined that the preliminary synthesis is completed and the in-situ zone melting purification stage begins. First, keep the temperature constant for 1 hour, and then heat up the 1st and 2nd temperature zones at the same time. The 1st temperature zone is heated to 550°C in 0.5 hours and maintained, and the 2nd temperature zone is heated to 670°C in 0.5 hours and kept constant for 0.5 hours. The other temperature zones are not operated. After the constant temperature is completed, the 2nd temperature zone is cooled to 550°C in 1 hour, and the 3rd temperature zone starts to heat up to 670°C in 0.5 hours and keeps constant for 0.5 hours. The other temperature zones are not operated. After the constant temperature is completed, it is cooled to 550°C in 1 hour. By analogy, the 4-7 temperature zones are operated in sequence according to the 2nd and 3rd temperature zones. The 1st temperature zone is always kept at 550°C. All temperature zones are heated and cooled in turn, so that the synthetic material in the quartz tube is melted and solidified in different areas according to a certain rule, and then melted and solidified again. This is repeated for no less than 3 times, and the pressure remains unchanged during this period. Step 8: After step 7, the cooling stage begins. The temperature drops to room temperature within 12 hours. The pressure is released, the sealed connector is opened, and the synthesized polycrystalline material is taken out. The 2mm horizontal ends of the polycrystalline material are discarded.

[0005] A further technical solution is: temperature zone 1 is longer than other temperature zones, temperature zones 2, 3, 4, 5, 6, and 7 are of equal length, temperature zone 1 is 2 cm apart from temperature zone 2, and temperature zones 2, 3, 4, 5, 6, and 7 are not spaced apart and are nested 1 cm apart from each other. All temperature zones are independently temperature controlled with a temperature control accuracy of 0.1-0.5 degrees.

[0006] A further technical solution is that the mass of the liquid sealing covering agent is 1 / 3 of the mass of the charge.

[0007] Compared with the prior art, the beneficial effects of the present invention are: 1. The present invention is easy to operate and can be synthesized in large quantities and produced in batches.

[0008] 2. The liquid seal covering agent seals all raw materials underneath it, which can effectively prevent the powder and melt from volatilizing and scattering at high temperature, prevent component segregation during reaction, and absorb excess impurities and unreacted powder; vacuum and inert gas balance the pressure and effectively control the formation of impurity phases and the infiltration of other impurities; the introduction of ultrasonic waves makes the synthesis reaction more uniform and thorough, so the polycrystalline material synthesized by the present invention has higher purity, no impurity phase, and high light transmittance.

[0009] 3. The present invention designs a unique temperature field, which not only meets the temperature gradient requirements during synthesis solidification, but also meets the individual zone temperatures to be reached by three polycrystalline in-situ zone melting after synthesis solidification. Zone melting can allow the synthesized polycrystalline material to be purified once more in-situ, and in-situ zone melting with different impurity segregation coefficients can well enrich impurities at both ends of the polycrystalline material. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 It is a structural schematic diagram of the present invention.

[0011] In the figure: 1. Quartz transmission rod; 2. Inert gas filling system; 3. Ultrasonic intervention system; 4. Sealed connector; 5. Vacuum system. DETAILED DESCRIPTION

[0012] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0013] In order to achieve high-quality synthesis of halogen perovskite polycrystals, the present invention provides a halogen perovskite polycrystal synthesis method, the polycrystal synthesis method comprising the following steps: The first step: uniformly mix high-purity PbBr2 powder and high-purity CsBr powder according to the atomic molar mass ratio of PbBr2:CsBr 1:0.55-0.58 and load them into a quartz boat. At the same time, put a solid liquid sealing covering agent with a weight of 1 / 3 of the weight of the loading into the quartz boat, and place the quartz boat in a quartz tube with one end of the quartz tube made into a round head seal and the other end open.

[0014] The liquid seal covering agent seals all raw materials underneath it, which can effectively prevent the powder and melt from volatilizing and scattering at high temperatures, prevent component segregation during reactions, and absorb excess impurities and unreacted powder.

[0015] One end of the quartz tube is made into a round head seal, and the round seal has a stronger pressure-bearing capacity.

[0016] Step 2: Place the quartz tube obtained in step 1 into the polycrystalline synthesis furnace of perovskite, and install a sealing connector 4 at the open end of the quartz tube to seal the inside of the quartz tube. The polycrystalline synthesis furnace has seven temperature zones arranged in sequence along the furnace cavity. Among them, temperature zone 1 is close to the sealing connector, and temperature zone 1 is located at the end of the quartz tube, which plays a role in maintaining the temperature of the temperature field. Therefore, temperature zone 1 is longer than other temperature zones. Figure 1 As shown, the quartz boat is located in temperature zones 2, 3, 4, 5, 6, and 7. Temperature zones 2, 3, 4, 5, 6, and 7 are of equal length. Temperature zone 1 is 2 cm apart from temperature zone 2 to prevent the temperature of temperature zone 1 from being transmitted to temperature zone 2, making it difficult to control the temperature of temperature zone 2 within the target range. Temperature zones 2, 3, 4, 5, 6, and 7 are not spaced apart and are nested with each other by 1 cm. All temperature zones are independently temperature controlled with a temperature control accuracy of 0.1-0.5 degrees.

[0017] Step 3: The sealing connector 4 is connected to the vacuum system 5, the inert gas filling system 2 and the ultrasonic intervention system 3 respectively, so that the vacuum system 5 can evacuate the quartz tube, the inert gas filling system 2 can introduce inert gas into the quartz tube, and the ultrasonic intervention system 3 can transmit ultrasonic waves into the quartz boat through a quartz transmission rod 1.

[0018] Step 4: After checking that all connections are in good condition, turn on the vacuum system 5 to make the vacuum degree in the quartz tube reach 10 - 5pa, remove the air in the quartz tube to reduce the adverse effects of air on the reaction. Turn off the vacuum pump, turn on the inert gas filling system 2, fill the quartz tube with inert gas to increase its pressure to 0.1-0.15mpa. The inert gas balances the pressure and effectively controls the formation of impurities and the infiltration of other impurities. Then use the temperature control system of the polycrystalline synthesis furnace to set the target parameters and temperature. After confirmation, turn on the power, and the polycrystalline synthesis furnace begins to heat up.

[0019] Step 5: Enter the melting reaction stage, all temperature zones are heated to 450°C in 30 minutes, and the temperature is kept constant for 1 hour, waiting for the solid liquid sealing covering agent to melt and become molten liquid. After 1 hour, the temperature is continued to rise. In 40 minutes, the temperature zone 1 close to the connector is heated to 550°C, and the other temperature zones are heated to 670°C. In the process of gradual temperature increase, the high-purity PbBr2 powder and the high-purity CsBr powder begin to gradually melt and react under the liquid liquid sealing covering agent. After the temperature stabilizes, the ultrasonic intervention system 3 is turned on. The ultrasonic frequency is 80-90KHZ. The constant temperature ultrasound is performed for 2 hours. The ultrasonic wave contacts the loaded quartz boat through the quartz transmission rod 1, and the ultrasonic wave is transmitted into the quartz boat. The material in the quartz boat will be excited by the ultrasonic wave and oscillate. The high temperature plus the ultrasonic oscillation will accelerate the material and react more evenly. It can also make the impurities detach faster and be absorbed by the liquid sealing covering agent, thereby reducing the component segregation of the material and improving the purity.

[0020] Step 6: After 2 hours of constant temperature ultrasound, observe the temperature. When there is no abnormal pressure, turn off the ultrasonic intervention system 3 and enter the next synthesis solidification stage. Enter the synthesis solidification program in the temperature control system. The temperature zones of the entire polycrystalline synthesis furnace will slowly cool down in an orderly manner according to the synthesis solidification program, starting from temperature zone 1 close to the sealing connector 4. Temperature zone 1 is cooled at a cooling rate of 4°C / h for 24 hours. When the temperature drops to 450-500°C, it remains at a constant temperature. Temperature zones 2, 3, 4, 5, 6, and 7 are cooled at intervals of 0.5 hours in the order of 2, 3, 4, 5, 6, and 7, respectively, at a cooling rate of 9°C / h for 24 hours. When the temperature of each temperature zone drops to 450-500°C, it remains at a constant temperature. The pressure must be kept constant throughout the synthesis stage. If there is any change, the inert gas filling system 2 must be used to inflate or deflate at any time to always control the pressure at the initial value before synthesis. The effects of sequential cooling in temperature zones 2-7 are: first, the polycrystalline material can be synthesized more densely without producing defects such as holes and bubbles; second, the solid-liquid interface gradually advances from temperature zone 2 to temperature zone 7, some impurities are enriched in the melt, and some are enriched in the solid. The impurities will condense to both sides and be enriched at both ends of the polycrystalline material, thereby ensuring the purity of the polycrystalline material after synthesis.

[0021] Step 7: Determine whether the synthesis is completed by temperature. When all the measured temperatures are between 450 and 500 °C, it can be determined that the preliminary synthesis is completed and the in-situ zone melting purification stage begins. First, keep the temperature constant for 1 hour, and then heat up the 1st and 2nd temperature zones at the same time. The 1st temperature zone is heated to 550 °C in 0.5 hours and maintained, the 2nd temperature zone is heated to 670 °C in 0.5 hours and kept constant for 0.5 hours, and the other temperature zones are not operated; after the constant temperature is completed, the 2nd temperature zone is cooled to 550 °C in 1 hour, and the 3rd temperature zone starts to heat up to 670 °C in 0.5 hours and keeps constant for 0.5 hours. The other temperature zones are not operated. After the constant temperature is completed, it is cooled to 550 °C in 1 hour, and the 4-7 temperature zones are operated in sequence according to the 2nd and 3rd temperature zones. The 1st temperature zone is always kept at 550 °C. All temperature zones are heated and cooled in turn, so that the synthetic material in the quartz tube is melted and solidified in different areas according to a certain rule, and then melted and solidified again, and repeated for no less than 3 times, during which the pressure remains unchanged.

[0022] This step is the in-situ zone melting purification stage, in which the perovskite polycrystalline material is repeatedly heated and cooled in the in-situ zone, and the polycrystalline material melts and solidifies repeatedly. The different segregation coefficients of impurities in the crystal are used. As the melting and solidification cycles are repeated, the solid-liquid interface gradually advances from temperature zone 1 to temperature zone 7. Some impurities are enriched in the melt and some in the solid. The impurities will segregate and enrich at both ends of the polycrystalline material, thereby improving the purity of the synthesized polycrystalline material. The more repeated times, the higher the purity of the polycrystalline obtained.

[0023] Step 8: After step 7, the temperature is lowered to room temperature within 12 hours, the pressure is released, the sealed connector 4 is opened, and the synthesized polycrystalline material is taken out. The 2 mm horizontal ends of the polycrystalline material are discarded because impurities are enriched at both ends of the polycrystalline material.

[0024] In summary, the present invention includes four stages, namely: melt reaction stage, synthesis solidification stage, in-situ zone melting and purification stage and temperature reduction and cooling stage.

[0025] During the melt reaction stage, the liquid seal covering agent seals all raw materials underneath it, which can effectively prevent the powder and melt from volatilizing and scattering at high temperature, prevent component segregation during the reaction, and absorb excess impurities and unreacted powder; vacuum and inert gas balance the pressure and effectively control the formation of impurity phases and the infiltration of other impurities; the introduction of ultrasonic waves makes the synthesis reaction more uniform and thorough, so the polycrystalline material synthesized by the present invention has higher purity, no impurity phases, and high transmittance.

[0026] During the in-situ zone melting purification stage, the in-situ area of ​​the perovskite polycrystalline material is heated and cooled repeatedly, and the polycrystalline material melts and solidifies repeatedly. The different segregation coefficients of impurities in the crystals are utilized. As the melting and solidification cycles are repeated, the solid-liquid interface gradually advances from temperature zone 1 to temperature zone 7. Some impurities are enriched in the melt and some in the solid. The impurities will segregate and enrich at both ends of the polycrystalline material, thereby ensuring the purity of the polycrystalline material after synthesis.

Claims

1. A method for synthesizing halogen perovskite polycrystals, characterized in that: The method comprises: The first step is to uniformly mix high-purity PbBr2 powder and high-purity CsBr powder according to the atomic molar mass ratio of 1:0.55-0.58 and put them into a quartz boat, put a liquid sealing covering agent into the quartz boat, and put the quartz boat into a quartz tube; Step 2: placing the quartz tube into a polycrystalline synthesis furnace, one end of which is provided with a sealed connector, wherein the polycrystalline synthesis furnace has seven temperature zones arranged in sequence along the furnace cavity; Step 3: The sealing connector is connected to the vacuum system, the inert gas filling system and the ultrasonic intervention system respectively, so that the vacuum system can evacuate the quartz tube, the inert gas filling system can introduce inert gas into the quartz tube, and the ultrasonic intervention system can transmit ultrasonic waves into the quartz boat; Step 4: After checking that all connections are in good condition, turn on the vacuum system and make the vacuum degree in the quartz tube reach 10 -5 pa, close the vacuum system, open the inert gas filling system, fill the quartz tube with inert gas to increase its pressure by 0.1-0.15mpa, and the polycrystalline synthesis furnace starts to heat up; Step 5: All temperature zones are heated to 450°C in 30 minutes and kept at a constant temperature for 1 hour; the liquid sealing cover agent melts into a molten state; the temperature zone 1 close to the connector is heated to 550°C in 40 minutes, and the other temperature zones are heated to 670°C. PbBr2 powder and CsBr powder begin to gradually melt and react under the liquid liquid sealing cover agent. After the temperature stabilizes, the ultrasonic intervention system is turned on and the temperature is kept constant for 2 hours. The ultrasonic frequency is 80-90KHZ; Step 6: Turn off the ultrasonic intervention system; each temperature zone of the polycrystalline synthesis furnace enters the cooling stage. Starting from the temperature zone close to the sealed connector, the temperature zones are 1, 2, 3, 4, 5, 6, and 7. The temperature of temperature zone 1 is cooled at a cooling rate of 4°C / h for 24 hours. When the temperature drops to 450-500°C, it remains at a constant temperature. The temperature zones 2, 3, 4, 5, 6, and 7 are cooled at intervals of 0.5 hours in sequence, and cooled at a cooling rate of 9°C / h for 24 hours. When the temperature of each temperature zone drops to 450-500°C, it remains at a constant temperature. The pressure must be kept constant throughout the synthesis stage. Step 7: When all the measured temperatures are between 450-500°C, it can be judged that the preliminary synthesis is completed, and the in-situ zone melting and purification stage begins. First, keep the temperature constant for 1 hour, and then heat up the 1st and 2nd temperature zones at the same time. The 1st temperature zone is heated to 550°C in 0.5 hours and maintained, and the 2nd temperature zone is heated to 670°C in 0.5 hours and kept constant for 0.5 hours. The other temperature zones are not operated; after the constant temperature is completed, the 2nd temperature zone is cooled to 550°C in 1 hour, and the 3rd temperature zone starts to heat up to 670°C in 0.5 hours and keeps constant for 0.5 hours. The other temperature zones are not operated. After the constant temperature is completed, it is cooled to 550°C in 1 hour, and the 4-7 temperature zones are operated in sequence according to the 2nd and 3rd temperature zones. The 1st temperature zone is always kept at 550°C. All temperature zones are heated and cooled in turn, so that the synthetic material in the quartz tube is melted and solidified in different areas according to a certain rule, and then melted and solidified again, and repeated for no less than 3 times, during which the pressure remains unchanged; Step 8: After step 7, cool to room temperature within 12 hours, release the pressure, open the sealed connector, take out the synthesized polycrystalline material, and discard 2mm at both ends of the polycrystalline material.

2. A method for synthesizing halogen perovskite polycrystals according to claim 1, characterized in that: Temperature zone 1 is longer than other temperature zones, and temperature zones 2, 3, 4, 5, 6, and 7 are of equal length. There is a 2cm interval between temperature zone 1 and temperature zone 2, and there is no interval between temperature zones 2, 3, 4, 5, 6, and 7, which are nested 1cm apart. All temperature zones are independently controlled, with a temperature control accuracy of 0.1-0.5 degrees.

3. The method for synthesizing halogen perovskite polycrystals according to claim 1, characterized in that: The mass of the liquid sealing covering agent is 1 / 3 of the mass of the charge.

Citation Information

Patent Citations

  • Preparation method of bromine-lead-cesium single crystals

    CN105483825A

  • Preparation method of bromine-lead-cesium monocrystal by horizontal moving zone melting

    CN108193271A